Theoretical and Numerical Study on the Natural Frequencies of Bridges With Corrugated Steel Webs. (August 2018) - Cao, Liang; Liu, Jiepeng; Frank Chen, Y.
Abstract: The dynamic characteristics including natural frequencies, mode shapes, and damping ratios are essential to investigate the vibration response of a structural system, in which the natural frequency is deemed the most important parameter. Research on the vertical natural frequencies of prestressed concrete (PC) box girders with corrugated steel webs (CSWs) is limited. In this research, the energy variation method proposed by E. Reissner and Galerkin method was adopted to study the single-span and multi-span continuous prismatic PC box girders with CSWs and simply-supported condition. To the accurately derive the formula for the vertical natural frequencies, the shear lag effect and shear effect from the box girder and CSWs, respectively, are considered. Numerical simulations were carried out to validate the theoretical solution. Sensitivity studies using the analytical equation were also conducted to investigate the effects of the waveform of CSWs, the outer top flange, and the thickness of corrugated steel webs.